Preliminary Second Five Year Plan Volume II Saharanpur District Uttar Pradesh - Planning Commission (Planning Commission, 1955)
Irrigation. By the time second five year plan is launched mostly 60% of the cultivated area would be under irrigation. Net. 10% of the area situated on the banks of the river cannot be brought under irrigation. For the remaining two state tube-wells out of the grant for minor irrigation schemes, 12 private tube-wells, 100 reasoner wells are proposed to be constructed. This would bring 13257 acres additional land under irrigation and thus almost the entire area would be under irrigation by the end of 1956-59.
Planning Department, Uttar Pradesh